System of Macroeconometric Models of the National Economy of Poland - Florczak, Waldemar; Świeczewska, Iwona; Welfe, Władysław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Economic growth is contemporarily becoming a function of more and more non-economic factors. From the point of view of aggregate social wealth economic conditions are an important but not an only element of its accumulation. Besides, there are numerous feedbacks between economic mechanisms of growth and socio-demographic and ecological conditions of development. That is why it seems crucial to explicitly incorporate such interlinks in macroeconomic models of Poland's long-run socio-economic development. This article presents main feedbacks existent between economic and non-economic determinants of development that are mapped by a system of macroeconometric models, named W8DS. The system comprises key aspects of sustainable development as well as numerous socio-economic issues. These are identified and discussed in the article.